2007
DOI: 10.1007/s11064-007-9461-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern and Splicing Function of Mouse ZNF265

Abstract: ZNF265 is a newly identified arginine/serine-rich (SR) protein and has two transcript isoforms (ZNF265-1 and ZNF265-2) that autoregulate between each other. Previous studies have shown that ZNF265 regulates the Tra2 beta isoform splicing. Here, we demonstrate that two ZNF-265 transcript isoforms are expressed in various mouse tissues and that ZNF265-1 is a major isoform. The ZNF265-1 protein level in the cerebral cortex is significantly lower in relative to other tissues. The recombinant proteins of both isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that ZRANB2 can alter the splicing of Tra2-␤, GLUR-B, and SMN2 reporter genes in splicing assays (6,7). The Tra2-␤ reporter gene contains 4 exons (Fig.…”
Section: The Binding Preferences Of Zranb2 Corroborate Functional Splmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that ZRANB2 can alter the splicing of Tra2-␤, GLUR-B, and SMN2 reporter genes in splicing assays (6,7). The Tra2-␤ reporter gene contains 4 exons (Fig.…”
Section: The Binding Preferences Of Zranb2 Corroborate Functional Splmentioning
confidence: 99%
“…It interacts with the spliceosomal proteins U1-70K and U2AF 35 and can alter the distribution of splice variants of GluR-B, SMN2, and Tra2␤ in minigene reporter assays (6,7). As such, ZRANB2 appears to regulate splice site choice.…”
mentioning
confidence: 99%
“…ZRANB2 contains 2 zinc finger domains, a C-terminal RS (arginine/serine-rich) domain, a glutamic acid-rich domain, and a nuclear localization sequence [4]. It interacts with components of the splicing factors U170K , U2AF35 , and XE7 and regulates splicing of GluR-B , SMN2 , and Tra2 β [57]. The 2 zinc finger domains recognize single-stranded RNA (ssRNA) and bind to a consensus AGGUAA motif [8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that ZNF265 proteins are co-immunoprecipitated with mRNAs and colocalize with splicing factors SMN, U1-70K, U2AF35 and SC35, indicating that ZNF265 is a novel component of spliceosomes (11,12). It has been known that many zinc finger proteins such as Gfi, GATA3, Egr-1, Aiolos, ZNF569 (13,14) play a crucial role in the immunoregulatory function of animals.…”
Section: Introductionmentioning
confidence: 99%